2014
DOI: 10.1007/s00424-014-1513-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces vasorelaxation by enhancing 4-aminopyridine-sensitive Kv currents through S-glutathionylation

Abstract: Hydrogen peroxide (H2O2) is an endothelium-derived hyperpolarizing factor. Since opposing vasoactive effects have been reported for H2O2 depending on the vascular bed and experimental conditions, this study was performed to assess whether H2O2 acts as a vasodilator in the rat mesenteric artery and, if so, to determine the underlying mechanisms. H2O2 elicited concentration-dependent relaxation in mesenteric arteries precontracted with norepinephrine. The vasodilatory effect of H2O2 was reversed by treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 80 publications
(104 reference statements)
1
39
0
Order By: Relevance
“…The remaining TRPV1-independent H 2 O 2 -mediated relaxation may be due to the compensatory mechanisms in V1KO mice such as KV channels (as indicated by 4-AP-mediated suppression of H 2 O 2 -mediated relaxation in V1KO mice). Indeed, we found that blocking KV channels with 4-AP together with SB366791 completely abolished H 2 O 2 -induced vasodilation, consistent with previous studies on KV channels, [2, 42, 47, 48]—reinforcing a role for TRPV1. BK Ca channels have been shown to contribute to arterial tone[33], however, unlike BK Ca -dependent H 2 O 2 -induced dilation in previous studies [3, 64], the BK Ca channel did not contribute significantly to the dilatory effect in our study, suggesting that the H 2 O 2 -dependent sensitivity of K + channels differs among vascular beds and perhaps species.…”
Section: Discussionsupporting
confidence: 91%
“…The remaining TRPV1-independent H 2 O 2 -mediated relaxation may be due to the compensatory mechanisms in V1KO mice such as KV channels (as indicated by 4-AP-mediated suppression of H 2 O 2 -mediated relaxation in V1KO mice). Indeed, we found that blocking KV channels with 4-AP together with SB366791 completely abolished H 2 O 2 -induced vasodilation, consistent with previous studies on KV channels, [2, 42, 47, 48]—reinforcing a role for TRPV1. BK Ca channels have been shown to contribute to arterial tone[33], however, unlike BK Ca -dependent H 2 O 2 -induced dilation in previous studies [3, 64], the BK Ca channel did not contribute significantly to the dilatory effect in our study, suggesting that the H 2 O 2 -dependent sensitivity of K + channels differs among vascular beds and perhaps species.…”
Section: Discussionsupporting
confidence: 91%
“…36 H 2 O 2 also activates smooth muscle K V 2.1 channels in rat mesenteric arteries through a similar mechanism via S-glutathionylation. 13 It remains to be determined whether H 2 O 2 -induced dilation involves redox modification of K V channels, or alternatively other intermediate signaling proteins as we reported previously for protein kinase G in H 2 O 2 -induced BK Ca activation. 7 …”
Section: Discussionmentioning
confidence: 85%
“…9 For instance, BK Ca channels contribute to H 2 O 2 -induced dilation in porcine coronary arteries. 10,11 In contrast, 4-aminopyridine (4-AP)-sensitive K V channels mediate dilation to H 2 O 2 in canine coronary arteries, 12 rat coronary and mesenteric arteries, 12, 13 and porcine coronary resistance arteries. 14 Using coronary arterioles from CAD subjects, we found that H 2 O 2 opens smooth muscle BK Ca channels to elicit smooth muscle hyperpolarization and relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…The potentiation was inhibited by tempol in the presence or absence of polyethylene glycol catalase (26), indicating a primary action of O 2 Ϫ rather than H 2 O 2 . Moreover, H 2 O 2 commonly acts as vasodilator in circulatory beds, such as cerebral, coronary, mesenteric, and skeletal muscle, and may function as an endotheliumdependent hyperpolarization factor and an activator of potassium channels (10,14,47,55,64,70); both dilator and hyperpolarizing actions are expected to blunt rather than potentiate pressure-induced myogenic constriction.…”
Section: Discussionmentioning
confidence: 99%